Understanding ratio of forces during early acceleration - Bezodis, N.; Colyer, S. L.; Nagahara, R.; Bayne, H.; Bezodis, I.; Morin, J.-B.; Murata, M.; Samozino, P. (ISBS Proceedings Archive (Michigan), 2019)
Ratio of forces (RF) were investigated during early acceleration by analysing block and standing starts in trained sprinters. RF variables over the initial block exit/push-off and the first four steps were determined from force plate data, and a simple macroscopic model was also applied to obtain RF variables from the velocity time-history over the entire acceleration phase. Large positive correlations existed between mean early acceleration RF and early acceleration performance from both standing (r = 0.82) and block (r = 0.89) starts, and both theoretical maximal RF and the rate of decline in RF combined to be important predictors (adj. R2 = 92-97%) of performance. From the simple macroscopic model, maximum RF was nearly perfectly correlated with early acceleration performance (r = 0.96) and thus appears to be an excellent simple measure for early acceleration